Are there three Subdivisions in the primate Subthalamic Nucleus? - Max C Keuken; Max C Keuken; Harry B.M. Uylings; Stefan eGeyer; Andreas eSchäfer; Robert eTurner; Birte U Forstmann; Birte U Forstmann (Frontiers Media S.A., 2012)
The prevailing academic opinion holds that the subthalamic nucleus (STN) consists of three parts, each anatomically distinct and selectively associated with cognitive, emotional, or motor functioning. We independently tested this assumption by summarizing the results from 33 studies on STN subdivisions in human and nonhuman primates. The studies were conducted from 1925 to 2010 and feature three different techniques: electrical lesions, anterograde and retrograde tracers, and classical cytoarchitectonics. Our results reveal scant evidence in support of a tripartite STN. Instead, our results show that the variability across studies is surprisingly large, both in the number of subdivisions and in their anatomical localization. We conclude that the number of subdivisions in the STN remains uncertain, and that academic consensus in support of a tripartite STN is presently unwarranted.